Pengaruh Literasi Keuangan dan Tingkat Pendapatan Terhadap Perilaku Menabung Pada Guru - Anggraini, Dwi Pertiwi (Journal of Business and Economics Research (JBE), 2024)
Financial literacy and level of income have an important influence on a person's saving behavior. The purpose of this study was to determine the effect of financial literacy and income levels on teachers' interest in saving behavior. This research uses quantitative methods. The population in this study were all teachers at Batang Kuis State Junior High School with a sample of 20 teachers who were taken randomly. The data collection technique in this study was to use a questionnaire. And the data analysis technique used is by performing multiple linear regression analysis with SPSS V.22. The results of this study partially state that financial literacy has a positive and significant effect on saving behavior. It can be seen that the tcount value for the financial literacy variable is 1.034 < ttable = 1.729 and a significant value is 0.005 <0.05, then Ho is rejected and Ha is accepted. The same goes for income levels. The results of this study partially state that the level of income has a positive and significant effect on saving behavior. It can be seen that the tcount value for the income level variable is 0.240 < ttable = 1.729 and a significant value is 0.005 <0.05, then Ho is rejected and Ha is accepted. And the results of this study simultaneously state that financial literacy and income levels together have a positive and significant effect on saving behavior of teachers. It can be seen that the value of Fcount = 7.537 is greater than the value of Ftable = 3.55.